Adaptation of Outcome-Based Education System in Pakistan for Engineering Disciplines and its Critical Evaluation - Farhan Haider; Afshan Ahmed Siddiqui; Syed Murtaza Ali (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2023)
Pakistan has become a part of the Washington Accord in 2017 and started making reforms in its education sector. Outcome-Based Education (OBE) has been emphasized by Pakistan Engineering Council (PEC) for the accreditation of all engineering degree programs. This paper presents some basic literature on the existing educational models in the world and the Outcome Based Education-OBE structure that has been implemented in Pakistan yet. Pakistan has successfully designed the Program Education Objectives (PEOs) and Program Learning Objectives (PLOs) for the academic sector. PEOs are the mission/vision statements that define the career and professional goals which the program is preparing students to achieve. PLOs are the quantifiable statements that define the knowledge and skills expertise of the students upon graduation ceremony. A survey has been conducted by employers to assess the skill level of fresh graduates against 12 PLOs of the OBE system in Pakistan. Of these, the PLOs related to four measurable statements namely: (i) Problem Analysis, (ii) Design of Solutions, (iii) Investigation, and (iv) Environment & Sustainability are found underperformance as surveyed from the industry sector following the performance of freshly graduated students. The survey also includes the Key Performance Indicator (KPI) evaluation of faculty members both from the department heads and the students too. This result shows underperformance of 15 % of the teaching faculty as per prescribed grading ranges. However, the OBE faces some difficulties as well and unfortunately, there are not so many graduates who entered into the industry after learning from OBE. It will, therefore, take some time to deliver the results of OBE implementation in Pakistan. Furthermore, some other education reforms from around the globe have been presented in this paper and some suggestions have been provided.